Pelatihan Pembuatan Hand Sanitizer yang Lembut di Kulit dalam Pencegahan Covid-19 di Kalangan Siswa SMA - Rizka Novia Atmadani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
The problem of Covid 19, which has become a pandemic, is a problem that must be prevented by implementing strict health protocols, especially with the use of Hand Sanitizers that have correct concentration and correct composition that effectively kill microorganisms on the hands. Making Hand Sanitizers using alcohol with 65- 95% concentration is one of the effective ingredients to break the chain of transmission of Covid-19. This training activity was carried out for students of PMR members of SMAN 7 Kediri through the stages of preparation, counseling with pretest and posttest, and the practice of making Hand Sanitizers. The Hand Sanitizer products that are produced are given to all students and the school. The pretest and posttest scores concluded that there was an increase in students' knowledge of the education provided. Hopefully, the students could make their Hand Sanitizer at home and could play a role in breaking the chain of the spread of Covid-19.